A 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms, its preparation method and application

By using the 1T/2H-MoS2 hybrid nanomaterials supported with Sn single atoms as electrocatalysts, the scarcity of precious metal electrocatalysts and the aggregation of single atoms are solved, and the electrochemical hydrogen evolution catalytic effect with high activity and high stability is achieved, and the electrocatalytic application prospects are good.

CN117822011BActive Publication Date: 2025-03-14ANHUI AGRICULTURAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410056600.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-16
Publication Date
2025-03-14
Estimated Expiration
2044-01-16

AI Technical Summary

Technical Problem

The scarcity, high cost and low durability of precious metals in existing electrocatalysts limit their large-scale and sustainable applications, and single-atom catalysts are prone to aggregation during electrocatalysis, resulting in activity and stability problems.

Method used

The 1T/2H-MoS2 hybrid nanomaterial supported by Sn single atoms was used as the electrochemical hydrogen evolution catalyst, and the 1T/2H-MoS2 heterojunction catalyst was synthesized by a simple two-step hydrothermal method, and the Sn single atom was loaded on the 1T/2H-MoS2 heterojunction by impregnation method.

Benefits of technology

The electrochemical hydrogen evolution catalytic effect with high activity and high stability is achieved, the use of precious metals is avoided, and the application of electrocatalytic applications is good, and excellent electrocatalytic activity is shown under the conditions of full pH.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117822011B_ABST
    Figure CN117822011B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electrocatalytic materials, and specifically relates to a 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms, and a preparation method and application thereof. The 1T / 2H-MoS2 carrier includes a monomer 2H-MoS2 and a monomer 1T-MoS2, and the monomer 2H-MoS2 and the monomer 1T-MoS2 are both spherical structures assembled from sheet structures, with nanoflowers growing on the surface, and the nanoflowers are assembled from a large number of nanosheets with exposed edges. In the 1T / 2H-MoS2 carrier, the monomer 1T-MoS2 grows on the surface of 2H-MoS2 and is completely wrapped on the surface of 2H-MoS2 to form a hollow spherical structure; the surface of the 1T / 2H-MoS2 is loaded with Sn in the form of a single Sn atom. As an electrocatalyst, the hybrid nanomaterial can perform an electrocatalytic hydrogen evolution reaction under full pH conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrocatalytic materials, and in particular relates to a 1T / 2H-MoS2 hybrid nanomaterial loaded with single Sn atoms, and a preparation method and application thereof. Background Art

[0002] Electrochemical water splitting is a feasible technology for producing green hydrogen. Acidic hydrogen evolution electrocatalysis has been widely used due to its high efficiency and high purity. Hydrogen is considered to be a highly non-polluting combustible gas, and its combustion product is only pure water, thus realizing the continuous large-scale storage and industrial utilization of renewable resources. Generally speaking, two half reactions, namely oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), occur at the anode and cathode, respectively, and together constitute the overall water splitting. They are both non-spontaneous reactions and require additional energy to overcome the reaction energy barrier of each half reaction. These processes consume a lot of energy, so effective electrocatalysts are needed to reduce the reaction overpotential. Generally, Ir / Ru oxides and Pt are widely used as benchmark electrocatalysts for OER and HER, respectively. Unfortunately, the large-scale and sustainability of noble metal-based electrocatalysts are limited by scarcity, high cost and moderate long-term durability. Among the published studies, late transition metal (Fe, Co, Ni, etc.) composite catalysts have been widely reported and deeply explored because of the excellent catalytic potential of late transition metals. However, the irreversible rapid agglomeration and severe deformation of nanoparticles result in low atomic utilization efficiency of composite materials. In this context, in order to successfully synthesize heterogeneous electrocatalysts, nanoparticles must be shrunk to nanodots or even single atoms. Since the concept of single-atom catalysts with maximum atomic efficiency was first proposed by Zhang et al., it has attracted widespread attention. However, the high surface energy makes single atoms more inclined to aggregate during electrocatalysis. Thanks to the strong metal-support interaction, the substrate can stabilize the single atoms and regulate the electronic structure of the single atoms. Therefore, it is particularly desirable to develop ideal supports for the controllable synthesis of single-atom catalysts to simultaneously solve the problems of activity and durability. In the past few decades, people have been committed to improving electrocatalysts to reduce costs and energy consumption. Summary of the invention

[0003] Based on the problems existing in the prior art, the present invention provides a 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms and a preparation method and application thereof. The hybrid nanomaterial described in the present invention is an electrochemical hydrogen evolution catalyst with high activity and high stability. While improving the catalyst performance, the use of precious metals is avoided, and it has good prospects for electrocatalytic application.

[0004] The present invention adopts the following technical solution:

[0005] A 1T / 2H-MoS2 hybrid nanomaterial loaded with single Sn atoms. The 1T / 2H-MoS2 carrier comprises a 2H-MoS2 monomer and a 1T-MoS2 monomer. Both the 2H-MoS2 monomer and the 1T-MoS2 monomer are spherical structures assembled from sheet structures, with nanoflowers grown on the surface. The nanoflowers are assembled from a large number of nanosheets with exposed edges. In the 1T / 2H-MoS2 carrier, the 1T-MoS2 monomer grows on the surface of the 2H-MoS2 and is completely wrapped on the surface of the 2H-MoS2 to form a hollow spherical structure. The surface of the 1T / 2H-MoS2 is loaded with Sn in the form of single Sn atoms.

[0006] The second object of the present invention is to provide a method for preparing a 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms, comprising the following steps:

[0007] S1. Preparation of bulk 2H-MoS2 nanomaterials:

[0008] S1.1, dissolving sodium molybdate in deionized water, and then adding glucose to obtain an aqueous solution;

[0009] S1.2, mixing n-butanol and glycerol evenly, and then adding dodecyltrimethylammonium bromide (CTAB) to obtain an oil phase solution;

[0010] S1.3, adding the aqueous solution dropwise to the oil phase solution, stirring and then sequentially adding concentrated hydrochloric acid and thiourea, stirring and then performing a hydrothermal reaction, after the reaction is completed, centrifugation and washing are performed to obtain a monodisperse MoS2 / CTAB precursor; then the precursor is subjected to annealing heat treatment to obtain a monodisperse hollow MoS2, i.e., a 2H-MoS2 monomer;

[0011] S2. Preparation of bulk 1T-MoS2 nanomaterials: Dissolve ammonium molybdate tetrahydrate in deionized water, add thiourea, stir for half an hour, then add ascorbic acid, and react at high temperature. After the reaction is completed, centrifuge and wash to obtain a black 1T-MoS2 monomer.

[0012] S3, putting the synthesized 2H-MoS2 monomer into the precursor solution of the 1T-MoS2 monomer in step S2, stirring with ultrasound, performing heat treatment reaction, obtaining a black substance 1T / 2H-MoS2 through centrifugal washing, and then annealing the 1T / 2H-MoS2;

[0013] S4. Disperse 1T / 2H-MoS2 in water, add ethylene glycol and stannous chloride solution in turn, react in a water bath, centrifuge and wash after the reaction, vacuum dry, and then transfer to a nitrogen atmosphere for heat treatment.

[0014] Furthermore, the molar ratio of sodium molybdate and glucose added in step S1.1 is 5:2, and the amount of deionized water added is 8 ml of deionized water per 1 mmol of sodium molybdate.

[0015] Furthermore, the volume ratio of n-butanol to glycerol in step S1.2 is 2:1, and the addition ratio of dodecyltrimethylammonium bromide (CTAB) to sodium molybdate is 1:1.

[0016] Furthermore, the specific operation of S1.3 is as follows: the aqueous phase solution is added dropwise to the oil phase solution, and concentrated hydrochloric acid and thiourea are added in sequence after stirring for 2 hours, and after stirring for 3 hours, the solution is added into a 100 mL polytetrafluoroethylene autoclave for reaction. After the reaction is completed, a monodisperse MoS2 / CTAB precursor is obtained after centrifugal washing; the precursor is then annealed and heat-treated to obtain a monodisperse hollow MoS2, i.e., a 2H-MoS2 monomer;

[0017] The addition ratio of concentrated hydrochloric acid and thiourea is 1 mL of concentrated hydrochloric acid corresponding to 7.5 mmol of thiourea, and the reaction conditions in the autoclave are a reaction temperature of 120° C.-200° C. and a reaction time of 5 h-30 h; the preferred conditions are a reaction temperature of 180° C. and a reaction time of 18 h.

[0018] The 2H-MoS2 formed under the reaction condition of 120℃ is uneven in size and the nanosheets on the surface are uneven, while the reaction temperature at 200℃ will cause 2H-MoS2 to become a solid structure, and the optimal reaction temperature is 180℃. When the reaction time is 5h, only sheet-like 2H-MoS2 can be formed, and it cannot self-assemble into a hollow sphere structure. When the reaction time is extended to 30h, the sheet-like 2H-MoS2 will self-assemble into a smooth solid sphere structure. The optimal reaction time is 18h, forming a hollow nanosphere structure.

[0019] Furthermore, the specific operation of step S2 is as follows: dissolving ammonium molybdate tetrahydrate in deionized water, adding thiourea first, stirring for half an hour, and then adding ascorbic acid, and performing a high-temperature reaction in a polytetrafluoroethylene autoclave. After the reaction is completed, centrifugation and washing are performed to obtain a black 1T-MoS2 monomer;

[0020] The molar ratio of ammonium molybdate tetrahydrate to thiourea is 1:1, the amount of deionized water added is 8 ml of deionized water for every 1 mmol of sodium molybdate, and the amount of ascorbic acid added is 5 mmol of ammonium molybdate tetrahydrate for 1 g of ascorbic acid; the conditions for high-temperature reaction are reaction temperature of 100°C-200°C and reaction time of 10h-30h, and the preferred conditions are reaction temperature of 170°C and reaction time of 18h.

[0021] 1T-MoS2 cannot be formed at a reaction temperature of 100°C, while a reaction temperature of 200°C will cause 1T-MoS2 to become 2H-MoS2, so the preferred reaction temperature is 170°C. At a reaction time of 10h, only flake 1T-MoS2 can be formed, which cannot self-assemble into a flower ball structure. When the reaction time is extended to 30h, the flake 1T-MoS2 will form 2H-MoS2, so the preferred reaction time is 18h to form a nano flower ball structure.

[0022] Furthermore, the specific operation of step S3 is as follows: putting the synthesized 2H-MoS2 monomer into the precursor solution of the 1T-MoS2 monomer in step S2, ultrasonically stirring for half an hour, heat treating for 5h-30h, obtaining a black substance 1T / 2H-MoS2 through centrifugal washing, and then annealing the 1T / 2H-MoS2;

[0023] The annealing conditions in step S3 are as follows: annealing temperature of 100°C-200°C, annealing time of 1h-4h, and heating rate of 5°C / min; preferably, annealing temperature of 150°C and annealing time of 2h.

[0024] When the annealing temperature is 100℃, 1T-MoS2 will not be able to combine more tightly with 2H-MoS2; when the annealing temperature is 200℃, 1T-MoS2 will become 2H-MoS2. Therefore, the annealing temperature of 150℃ and the annealing time of 1h will result in insufficient annealing of the sample 1T / 2H-MoS2. The annealing time of 4h will also cause 1T-MoS2 to become 2H-MoS2. Therefore, the annealing time of 2h is selected as the optimal principle.

[0025] Further, the specific operation of step S4 is as follows: 1T / 2H-MoS2 is dispersed in water, ethylene glycol and stannous chloride solution are added in sequence, and reacted in a water bath at 50-100°C for 2h-15h, centrifuged and washed after the reaction, placed in a vacuum environment at 50-60°C for 10-12h, and then transferred to a nitrogen atmosphere for heat treatment;

[0026] The concentration of tin in the stannous chloride solution is 0.552 mg / ml, and the addition ratio of ethylene glycol to water is 1:10;

[0027] The preferred conditions for the water bath reaction are a reaction temperature of 70° C. and a reaction time of 10 hours.

[0028] Ethylene glycol cannot reduce divalent tin ions at 50°C, but will cause the generation of tin particles at 100°C. The optimal water bath reaction temperature is 70°C. A water bath reaction time of 2h will result in the inability to adsorb tin ions, while a water bath reaction time of 15h will result in too much adsorption of tin ions to form particles. The optimal water bath reaction time is 10h.

[0029] Another object of the present invention is to provide the application of the 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms as an electrocatalyst.

[0030] Furthermore, the 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms has excellent activity in the electrocatalytic hydrogen evolution reaction under all pH conditions.

[0031] Beneficial technical effects of the present invention: The present invention obtains a 1T / 2H-MoS2-loaded Sn single-atom hybrid nanomaterial by selecting and regulating the type of precursor and the distribution ratio of each component. The preparation process is simple, reproducible, low-cost, environmentally friendly, and conducive to its industrial application.

[0032] The Sn single-atom hybrid nanomaterial is loaded on the 1T / 2H-MoS2 of the present invention, and the formation of the heterogeneous junction and the Sn single atom can effectively improve the hydrogen evolution activity and stability of the MoS2 electrocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram of the synthesis of the 1T / 2H-MoS2-Sn reactor described in the example.

[0034] Figure 2 a is the SEM image of 2H-MoS2 nanomaterial; 2b is the SEM image of 2H-MoS2-Sn nanomaterial;

[0035] Figure 3 a is a SEM image of the 1T-MoS2 nanomaterial; Figure 3 b is a SEM image of the 1T-MoS2-Sn nanomaterial;

[0036] Figure 4 a is a SEM image of the 1T / 2H-MoS2 nanomaterial; Figure 4 b is the SEM image of 1T / 2H-MoS2-Sn reactor;

[0037] Figure 5 is a TEM image of the 2H-MoS2 nanomaterial;

[0038] Figure 6 is a TEM image of the 2H-MoS2-Sn nanomaterial;

[0039] Figure 7 TEM image of the 1T-MoS2 nanomaterial;

[0040] Figure 8 is a TEM image of the 1T-MoS2-Sn nanomaterial;

[0041] Fig. 9 TEM image of the 1T / 2H-MoS2 nanomaterial;

[0042] Fig.10 TEM image of the 1T / 2H-MoS2-Sn reactor;

[0043] Fig.11 is the HRTEM image of the 1T / 2H-MoS2-Sn nanomaterial;

[0044] Fig.12 This is a spherical aberration electron microscope picture of the surface of the 1T / 2H-MoS2-Sn nanomaterial;

[0045] Fig.13 A high-rate HAADF image of the 1T / 2H-MoS2-Sn nanomaterial;

[0046] Fig.14 is the distribution of Mo element in the 1T / 2H-MoS2-Sn nanomaterial;

[0047] Fig.15 is the distribution of S element in the 1T / 2H-MoS2-Sn nanomaterial;

[0048] Fig.16 is the distribution of Sn element in the 1T / 2H-MoS2-Sn nanomaterial;

[0049] Fig.17 XRD patterns of the 2H-MoS2, 1T-MoS2, 2H-MoS2-Sn, 1T-MoS2-Sn, 1T / 2H-MoS2 and 1T / 2H-MoS2-Sn hybrid nanomaterials;

[0050] Fig.18 Raman graphs of 2H-MoS2, 1T-MoS2, 1T / 2H-MoS2 and 1T / 2H-MoS2-Sn hybrid nanomaterials;

[0051] Fig.19 The X-ray absorption near-edge structures of the Sn-foil, 1T / 2H-MoS2-Sn, and SnO2;

[0052] Fig. 20Fourier transform extended x-ray absorption fine structure for the Sn-foil, 1T / 2H-MoS2-Sn, and SnO2;

[0053] Fig.21 is the wavelet transform image of the Sn-foil;

[0054] Fig. 22 is the wavelet transform image of the 1T / 2H-MoS2-Sn;

[0055] Fig.23 is the wavelet transform image of SnO2;

[0056] Fig.24 A comparison diagram of the electrochemical performance of the 2H-MoS2, 1T-MoS2, 2H-MoS2-Sn, 1T-MoS2-Sn, 1T / 2H-MoS2 and 1T / 2H-MoS2-Sn hybrid nanomaterials under acidic conditions;

[0057] Fig.25 The Tafel slope graphs of the 2H-MoS2, 1T-MoS2, 2H-MoS2-Sn, 1T-MoS2-Sn, 1T / 2H-MoS2 and 1T / 2H-MoS2-Sn hybrid nanomaterials;

[0058] Fig.26 Impedance slope diagrams of the 2H-MoS2, 1T-MoS2, 2H-MoS2-Sn, 1T-MoS2-Sn, 1T / 2H-MoS2 and 1T / 2H-MoS2-Sn hybrid nanomaterials;

[0059] Fig. 27 The performance and Tafel slope diagram of the 1T / 2H-MoS2 hybrid nanomaterial loaded with different single atoms;

[0060] Fig.28 The LSV performance comparison of the 1T / 2H-MoS2-Sn hybrid nanomaterial under different pH conditions;

[0061] Fig.29 The stability of the 1T / 2H-MoS2-Sn hybrid nanomaterial at different current densities;

[0062] Fig.30 This is a comparison diagram of the LSV performance of the 1T / 2H-MoS2-Sn hybrid nanomaterial before and after the reaction;

[0063] Fig.31 is the in-situ XRD pattern of the 1T / 2H-MoS2-Sn hybrid nanomaterial;

[0064] Fig.32This is the in-situ Raman image of the 1T / 2H-MoS2-Sn hybrid nanomaterial. DETAILED DESCRIPTION

[0065] The technical solution of the present invention is described in detail below through specific embodiments.

[0066] The present invention adopts a simple two-step hydrothermal method to synthesize the 1T / 2H-MoS2 heterojunction catalyst, and uses an impregnation method to load Sn single atoms on the 1T / 2H-MoS2 heterojunction. Figure 1 As shown, first, we use the micelle-constrained microemulsion method to synthesize 2H-MoS2, then put 2H-MoS2 into the precursor solution of 1T-MoS2 to hydrothermally synthesize 1T / 2H-MoS2, and then load Sn single atoms on the 1T / 2H-MoS2 heterojunction by adsorption.

[0067] Example 1

[0068] Preparation of 2H-MoS2 nanomaterials:

[0069] 5mmol sodium molybdate was dissolved in 40mL deionized water, and then 2mmol glucose was added to obtain an aqueous solution; 20mL n-butanol and 10mL propylene glycol were mixed evenly, and then 5mmol dodecyltrimethylammonium bromide (CTAB) was added to obtain an oil solution; the aqueous solution was added dropwise to the oil solution, and after stirring for 2h, 4mL hydrochloric acid and 30mmol thiourea were added in sequence, and after stirring for 3h, the reaction was carried out in a polytetrafluoroethylene autoclave at a temperature of 200°C and a reaction time of 18h. After the reaction was completed, a monodisperse MoS2 / CTAB precursor was obtained after centrifugal washing; the precursor was then annealed and heat treated to obtain a monodisperse hollow MoS2.

[0070] The SEM image of 2H-MoS2 described in this embodiment is as follows Figure 2 As shown in a, the TEM image of 2H-MoS2 described in this embodiment is as shown in Figure 5 As shown, the XRD pattern of 2H-MoS2 prepared in this embodiment is as follows Fig. 20 shown.

[0071] Example 2

[0072] Preparation of 1T-MoS2 nanomaterials:

[0073] Dissolve 5mmol of ammonium molybdate tetrahydrate in 40ml of water and add 5mmol of thiourea. After stirring for half an hour, add 1g of ascorbic acid and react in a polytetrafluoroethylene autoclave at a temperature of 200°C for 24h. After the reaction is completed, black 1T-MoS 2。

[0074] The SEM image of 1T-MoS2 described in this embodiment is as follows Figure 3 As shown in a, the TEM image of 1T-MoS2 described in this embodiment is as follows Figure 7 As shown, the XRD pattern of 1T-MoS2 prepared in this example is as follows Fig. 20 shown.

[0075] Example 3

[0076] Preparation of 2H-MoS2-Sn hybrid nanomaterials:

[0077] Disperse 2H-MoS2 in water, add ethylene glycol and stannous chloride solution in turn, the addition ratio of ethylene glycol to water is 1:10; the concentration of tin in the stannous chloride solution is 0.552 mg / ml, and react in a water bath at 70-80℃ for 15h. After the reaction, centrifuge and wash, place in a vacuum environment at 50-60℃ to dry for 10-12h, and then transfer to a nitrogen atmosphere for heat treatment.

[0078] The SEM image of 2H-MoS2-Sn described in this embodiment is as follows Figure 2 As shown in b, the TEM image of 2H-MoS2-Sn described in this embodiment is as follows Figure 6 As shown, the XRD pattern of 2H-MoS2-Sn prepared in this embodiment is as follows Fig. 20 shown.

[0079] Example 4

[0080] Preparation of 1T-MoS2-Sn hybrid nanomaterials:

[0081] 1T-MoS2 was dispersed in water, and ethylene glycol and stannous chloride solution were added in turn, the addition ratio of ethylene glycol to water was 1:10; the concentration of tin in the stannous chloride solution was 0.552 mg / ml, and the reaction was carried out in a water bath at 70-80°C for 15 hours. After the reaction, the reaction was centrifuged and washed, and the reaction was placed in a vacuum environment at 50-60°C for 10-12 hours, and then transferred to a nitrogen atmosphere for heat treatment.

[0082] The SEM image of 1T-MoS2-Sn in this embodiment is as follows Figure 3 As shown in b, the TEM image of 1T-MoS2-Sn in this embodiment is as follows Figure 8 As shown, the XRD pattern of 1T-MoS2-Sn prepared in this embodiment is as follows Fig. 20 shown.

[0083] Example 5

[0084] Preparation of 1T / 2H-MoS2 hybrid nanomaterials:

[0085] 2H-MoS2 was dispersed in water, and 5mmol thiourea and 1g ascorbic acid were added in sequence in a polytetrafluoroethylene autoclave. After the reaction was completed, black 1T / 2H-MoS2 was obtained by centrifugal washing.

[0086] The SEM image of 1T / 2H-MoS2 described in this embodiment is as follows Figure 4 As shown in a, the TEM image of 1T / 2H-MoS2 described in this embodiment is as follows Fig. 9 As shown, the XRD pattern of 1T-MoS2-Sn prepared in this embodiment is as follows Fig. 20 shown.

[0087] Example 6

[0088] Preparation of 1T / 2H-MoS2-Sn hybrid nanomaterials:

[0089] Disperse 1T / 2H-MoS2 in water, add ethylene glycol and stannous chloride solution in turn, and react in a water bath at 70-80℃ for 15h. After the reaction, centrifuge and wash, place in a vacuum environment at 50-60℃ to dry for 10-12h, and then transfer to a nitrogen atmosphere for heat treatment.

[0090] The SEM image of 1T / 2H-MoS2-Sn described in the embodiment is as follows Figure 4 As shown in b, the TEM image of 1T / 2H-MoS2-Sn described in this embodiment is as follows Fig.10 As shown, the XRD pattern of 1T-MoS2-Sn prepared in this embodiment is as follows Fig. 20 shown.

[0091] Through the SEM images of the materials of Examples 1-6 ( Figure 2-4 ) By comparison, it was found that both 2H-MoS2 and 1T-MoS2 are spherical structures assembled into lamellar structures, and 1T-MoS2 grows on the surface of 2H-MoS2. It is obvious that the surface of 1T / 2H-MoS2 is rougher, and no Sn particles or clusters are found. The nanoflowers grown on the surface are assembled by a large number of nanosheets with exposed edges, with a lateral size of 300-500nm. In the two-dimensional nanostructure, the pores between the thin sheets are conducive to the transmission of electron injection or ion diffusion, which is beneficial to its application in electrochemical energy storage.

[0092] like Figure 5-9As shown in the figure, low-magnification TEM images show the hollow structure of 2H-MoS2 and the flower ball lamellar structure of 1T-MoS2 respectively. No Sn particles or clusters were found on 2H-MoS2 and 1T-MoS2. At the same time, through low-magnification TEM, it was found that 1T / 2H-MoS2 is obviously much thicker than the monomer 2H-MoS2. The shell thickness of the original 2H-MoS2 is about 50nm, while although 1T / 2H-MoS2 is still a hollow structure, the shell thickness reaches about 100nm, indicating that 1T-MoS2 is completely wrapped on the surface of 2H-MoS2, and no Sn particles or clusters appear on the surface of 1T / 2H-MoS2-Sn, as shown in the figure. Fig.10 .

[0093] Fig.11 The high-resolution TEM image further shows the crystal structure of each layer. Two obvious symmetrical lattice regions can be clearly observed in the image; the (101) plane of the 2H phase has a lattice distance of 0.64nm, and the plane spacing of the triangular lattice region is about 0.75nm, representing the (101) plane of 1T-MoS2. According to the high-angle annular dark field (HAADF) image ( Figure 12-13 ), the high brightness of the circle mark can be easily found on the surface of 1T-MoS2 ( Fig.12 ), the light intensity of each atom is positively correlated with its atomic number, and Sn atoms should be brighter than Mo and S atoms. Therefore, these bright spots may be the locations of Sn atoms, which confirms that Sn may be loaded on the surface of 1T-MoS2 in the form of single atoms.

[0094] Figure 14-16 This is the emission dispersive spectroscopy (EDS) analysis of the 1T / 2H-MoS2-Sn nanomaterial; it shows that the S, Mo and Sn atoms of 1T / 2H-MoS2-Sn are evenly distributed throughout the nanosheet. Fig.17 The XRD patterns of the 2H-MoS2, 1T-MoS2, 2H-MoS2-Sn, 1T-MoS2-Sn, 1T / 2H-MoS2 and 1T / 2H-MoS2-Sn hybrid nanomaterials are shown in Figure 2. By comparison, the XRD peaks of the synthesized samples are relatively sharp, indicating a high degree of crystallization. Secondly, the XRD spectrum of the 2H-MoS2 sample is the same as that reported in the literature, with a (002) peak at around 14.38°, which once again confirms that it is a 2H phase. The first peak of the 1T-MoS2 sample is located at around 9.16°, and the corresponding lattice distance is 0.965nm. This is because the insertion of ascorbic acid causes lattice distortion and is accompanied by an increase in interlayer distance. And with the embedding of Sn single atoms, the XRD spectrum does not have Sn peaks, which also proves from the side that Sn embedding does not change the properties of 1T / 2H-MoS2.

[0095] Fig.18 The Raman graphs of the 2H-MoS2, 1T-MoS2, 1T / 2H-MoS2 and 1T / 2H-MoS2-Sn hybrid nanomaterials are shown in Table 1. By comparison, the Raman graphs of the 2H-MoS2, 1T-MoS2, 1T / 2H-MoS2 and 1T / 2H-MoS2-Sn hybrid nanomaterials are shown in Table 1. -1 The two peaks at are E 1 2g and A 1g The vibration configurations at 147, 234, 284, 336 cm -1 Another group of characteristic peaks at the position correspond to the J1, J2 and J3 modes of 1T-MoS2. The Raman spectrum of 1T / 2H-MoS2 shows that the characteristic peaks of both phases exist, which further confirms the successful preparation of 1T / 2H-MoS2. It is worth noting that the embedding of single Sn atoms does not change the characteristic peaks, which reflects from the side that the introduction of Sn will not change the original structure. In order to further determine the chemical valence state and local structure of 1T / 2H-MoS2-Sn, the evolution of the local coordination environment in Sn-induced MoS2 was studied by X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) techniques. In contrast, the position of the absorption edge in the X-ray absorption near-edge structure (XANES) of 1T / 2H-MoS2-Sn is different from that of Sn and SnO2. Its position in the prepared material is between that of Sn foil and SnO2, such as Fig.19 See Fig. 20 The Fourier transform extended X-ray absorption fine structure (FT-EXAFS) results show that no Sn-Sn was detected in 1T / 2H-MoS2-Sn, indicating that the Sn element mainly exists in the form of single atoms. Figure 21-23 , in the wavelet transform (WT) plot, it is further confirmed that the existence of Sn-S bonds and S-Sn-S bonds in 1T / 2H-MoS2-Sn is higher than that in Sn foil. The above results indicate that Sn is coordinated with S atoms on the surface of 1T / 2H-MoS2.

[0096] The 2H-MoS2, 1T-MoS2, 2H-MoS2-Sn, 1T-MoS2-Sn, 1T / 2H-MoS2 and 1T / 2H-MoS2-Sn hybrid nanomaterials obtained in Examples 1, 2, 3, 4, 5 and 6 were used as electrocatalysts for electrocatalytic hydrogen evolution reaction, and the specific process was as follows:

[0097] The HER activity of the prepared materials was electrochemically tested in 0.5 MH2SO4 electrolyte using an electrochemical workstation (CHI760E, CHInstrumentsIns., Shanghai, China). The HER performance in 0.5 MH2SO4 was studied using a standard three-electrode system. The 1T / 2H-MoS2-Sn hybrid nanomaterial was prepared into a 1 mg / ml solution (80% water: 10% ethanol: 10% nafion solution) and then dropped into nickel foam (0.5×0.5 cm 2 ) was used as the working electrode; a saturated calomel electrode was used as the reference electrode, and a platinum sheet was used as the counter electrode.

[0098] The linear sweep voltammetry (LSV) curves were obtained in the range of -0.3-0.1 V for RHE at a rate of 5 mVs -1 The scan rate was measured, and the results are as follows Fig.24 As shown. The Tafel curve is calculated according to the formula η=a+blog(abs(j)) (b: Tafel slope, j: current density), and the result is as follows Fig.25 Electrochemical impedance spectroscopy (EIS) was measured at -0.45 V for RHE, 0.1 Hz for low frequency, and 1*10 for high frequency. 6 The results under HZ conditions are as follows Fig.26 The long-term electrochemical stability test of 1T / 2H-MoS2-Sn is shown in Fig.28 shown. Fig.24 The scan rate is 5 mV s −1 Polarization curves at 2H-MoS2 show poor HER performance at a current density of 10Ma cm −2 When the overpotential is about 276mV, 1T-MoS2 can reach 264mV, 1T / 2H-MoS2 can reach 140mV, 2H-MoS2-Sn can reach 123mV, and 1T-MoS2-Sn can reach 87mV. In contrast, when Sn single atoms are embedded, the performance of 1T / 2H-MoS2-Sn reaches 15mV, which is much lower than the commercial Pt / C catalyst 34mV. The HER kinetics of the catalyst are determined by studying the corresponding Tafel slope. A lower Tafel slope usually leads to an increase in the HER rate, such as Fig.25 As shown, 2H-MoS2-Sn (99.6 mV dec -1 )) has a Tafel slope smaller than that of 2H-MoS2 (140 mV dec -1 )、1T-MoS2-Sn(69.7 mVdec -1 )) has a Tafel slope smaller than that of 1T-MoS2 (123mV dec -1), 1T / 2H-MoS2-Sn(22.9 mV dec -1 )) has a much smaller Tafel slope than 1T / 2H-MoS2 (112 mV dec -1 )) and Pt / C (31.4 mV dec -1 )) indicates that 1T / 2H-MoS2-Sn has faster catalytic kinetics and higher HER catalytic activity. The catalytic kinetics at an overpotential of 15 mV was further studied by electrochemical impedance spectroscopy (EIS). Fig.26 As shown, the results show that the charge transfer resistance (Rct) value of 1T / 2H-MoS2-Sn is smaller than that of 2H-MoS2, 1T-MoS2, 1T / 2H-MoS2, 2H-MoS2-Sn and 1T-MoS2-Sn, confirming that 1T / 2H-MoS2-Sn has fast electron transfer and suitable HER kinetics at the interface between acidic electrolyte and electrocatalyst. It is worth noting that the smallest Rct of 1T / 2H-MoS2-Sn indicates that the native electron transfer speed of 1T / 2H-MoS2-Sn is faster than that of 2H-MoS2, 1T-MoS2, 1T / 2H-MoS2, 2H-MoS2-Sn and 1T-MoS2-Sn.

[0099] The single atoms that do not pass through are loaded on the surface of the phase junction by impregnation for catalysis. The HER catalytic performance and Tafel slope comparison of Sn, lanthanide metals and transition metals (Fe, Co, Ni) are tested. Fig. 27 As shown, it was found that Sn atoms have a good catalytic effect. The results show that 1T / 2H-MoS2-Sn exposes more effective active sites than 2H-MoS2, 1T-MoS2, 1T / 2H-MoS2, 2H-MoS2-Sn and 1T-MoS2-Sn. This is because the embedding of Sn in 1T / 2H-MoS2-Sn provides more active sites for HER catalysis. Under all pH conditions, 1T / 2H-MoS2-Sn is used for electrocatalytic water splitting, such as Fig.28 As shown, it has good electrocatalytic activity in acidic, neutral and alkaline conditions.

[0100] The long-term electrochemical stability of 1T / 2H-MoS2-Sn is shown in Fig.29 At 10 mA cm -2 , 20mA cm -2 、50mAcm -2 and 100mA cm -2 Continuous tests were carried out under 40 ℃ to investigate the durability of 1T / 2H-MoS2-Sn electrocatalyst. Fig.29The results show that after 120 h of continuous operation at high and low current densities, the overpotential only slightly decays, confirming its excellent stability and flexibility.

[0101] The 1T / 2H-MoS2-Sn hybrid nanomaterial prepared by the present invention has a good electrocatalytic hydrogen evolution effect under acidic conditions. -2 The overpotential is 15 mV at a current density of 1.37 W, and the Tafel slope is as low as 22.9 mVdec. -1 And it can maintain good stability within 24 hours. The Nyquist plots of several catalysts show that the charge transfer resistance (Rct) is significantly reduced after loading single atoms, among which the Rct value of 1T / 2H-MoS2-Sn hybrid nanomaterials is much lower than that of bulk MoS2, showing the lowest charge transfer resistance and the fastest charge transfer kinetics, indicating that superior charge transfer kinetics is conducive to a fast HER process.

[0102] Fig.30 The figure is a comparison of the LSV performance of the 1T / 2H-MoS2-Sn hybrid nanomaterial before and after the reaction. By comparing the LSV performance of the samples before and after the reaction, it is found that only a slight decay occurs, which is only 1mV decayed at a current density of 50 and 2mV decayed at a current density of 100. On-site characterization is carried out to monitor the evolution of structural information in 1T / 2HMoS2-Sn. When the applied voltage is from 0.14 to 0.54V, there is no obvious change in the XRD of 1T / 2HMoS2-Sn, as shown in Fig. Fig.31 , from the side reaction to prepare the stability of the material. Fig.32 From the in situ Raman spectra shown in Figure 2, the E 1 2g , A 1g The J1, J2, and J3 vibrations always exist with the increase of applied voltage without obvious differences, which proves the stable performance of 1T / 2H-MoS2-Sn.

Claims

1. A method for preparing a 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms, characterized in that: The steps include: S1. Preparation of bulk 2H-MoS2 nanomaterials: S1.1, dissolving sodium molybdate in deionized water, and then adding glucose to obtain an aqueous solution; S1.2, n-butanol and glycerol are mixed evenly, and then dodecyltrimethylammonium bromide (CTAB) is added to obtain an oil phase solution; S1.3, adding the aqueous solution dropwise to the oil phase solution, stirring and then sequentially adding concentrated hydrochloric acid and thiourea, stirring and then performing a hydrothermal reaction, after the reaction is completed, centrifugation and washing are performed to obtain a monodisperse MoS2 / CTAB precursor; then the precursor is subjected to annealing heat treatment to obtain a monodisperse hollow MoS2, i.e., a 2H-MoS2 monomer; S2. Preparation of bulk 1T-MoS2 nanomaterials: Dissolve ammonium molybdate tetrahydrate in deionized water, add thiourea, stir for half an hour, then add ascorbic acid, and react at high temperature. After the reaction is completed, centrifuge and wash to obtain a black 1T-MoS2 monomer. S3, putting the synthesized 2H-MoS2 monomer into the precursor solution of the 1T-MoS2 monomer in step S2, stirring with ultrasound, performing heat treatment reaction, obtaining a black substance 1T / 2H-MoS2 through centrifugal washing, and then annealing the 1T / 2H-MoS2; S4, 1T / 2H-MoS2 is dispersed in water, ethylene glycol and stannous chloride solution are added in sequence, and a water bath reaction is carried out. After the reaction is completed, centrifugal washing is performed, vacuum drying is performed, and then the mixture is transferred to a nitrogen atmosphere for heat treatment; The 1T / 2H-MoS2 carrier includes monomer 2H-MoS2 and monomer 1T-MoS2. Both the monomer 2H-MoS2 and the monomer 1T-MoS2 are spherical structures assembled from lamellar structures, with nanoflowers grown on the surface. The nanoflowers are assembled from a large number of nanosheets with exposed edges. In the 1T / 2H-MoS2 carrier, the monomer 1T-MoS2 grows on the surface of 2H-MoS2 and is completely wrapped on the surface of 2H-MoS2 to form a hollow spherical structure. The surface of the 1T / 2H-MoS2 is loaded with Sn in the form of single Sn atoms.

2. The method for preparing the 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms according to claim 1, characterized in that: The molar ratio of sodium molybdate and glucose added in step S1.1 is 5:2, and the amount of deionized water added is 8 ml of deionized water for every 1 mmol of sodium molybdate.

3. The method for preparing the 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms according to claim 1, characterized in that: The volume ratio of n-butanol to glycerol in step S1.2 is 2:1, and the addition ratio of dodecyltrimethylammonium bromide (CTAB) to sodium molybdate is 1:

1.

4. The method for preparing the 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms according to claim 1, characterized in that: The specific operation of S1.3 is as follows: the aqueous solution is added dropwise to the oil phase solution, and concentrated hydrochloric acid and thiourea are added in sequence after stirring for 2 hours. After stirring for 3 hours, the solution is added to a 100 mL polytetrafluoroethylene autoclave for reaction. After the reaction is completed, a monodisperse MoS2 / CTAB precursor is obtained after centrifugal washing; the precursor is then annealed and heat treated to obtain a monodisperse hollow MoS2, i.e., a 2H-MoS2 monomer. The addition ratio of concentrated hydrochloric acid and thiourea is 1 mL of concentrated hydrochloric acid corresponding to 7.5 mmol of thiourea, and the reaction conditions in the autoclave are a reaction temperature of 120° C.-200° C. and a reaction time of 5 h-30 h.

5. The method for preparing the 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms according to claim 1, characterized in that: The specific operation of step S2 is as follows: dissolve ammonium molybdate tetrahydrate in deionized water, add thiourea first, stir for half an hour, then add ascorbic acid, and carry out high-temperature reaction in a polytetrafluoroethylene autoclave. After the reaction is completed, centrifuge and wash to obtain a black 1T-MoS2 monomer; The molar ratio of ammonium molybdate tetrahydrate to thiourea is 1:1, the amount of deionized water added is 8 ml of deionized water for every 1 mmol of sodium molybdate, and the amount of ascorbic acid added is 5 mmol of ammonium molybdate tetrahydrate for 1 g of ascorbic acid; the conditions for high-temperature reaction are reaction temperature of 100°C-200°C and reaction time of 10h-30h.

6. The method for preparing the 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms according to claim 1, characterized in that: The specific operation of step S3 is as follows: putting the synthesized 2H-MoS2 monomer into the precursor solution of the 1T-MoS2 monomer in step S2, ultrasonically stirring for half an hour, heat treating for 5h-30h, and obtaining the black substance 1T / 2H-MoS2 through centrifugal washing, and then annealing the 1T / 2H-MoS2; The annealing treatment conditions in step S3 are as follows: the annealing temperature is 100° C.-200° C., the annealing time is 1 h-4 h, and the heating rate is 5° C. / min.

7. The method for preparing the 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms according to claim 1, characterized in that: The specific operation of step S4 is as follows: 1T / 2H-MoS2 is dispersed in water, ethylene glycol and stannous chloride solution are added in sequence, and reacted in a water bath at 50-100°C for 2h-15h. After the reaction, the mixture is centrifuged and washed, placed in a vacuum environment at 50-60°C for drying for 10-12h, and then transferred to a nitrogen atmosphere for heat treatment; The concentration of tin in the stannous chloride solution is 0.552 mg / ml, and the addition ratio of ethylene glycol to water is 1:

10.

8. Use of the 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms prepared by the preparation method as claimed in claim 1 as an electrocatalyst.

9. The use of the 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms as claimed in claim 8 as an electrocatalyst, characterized in that: The 1T / 2H-MoS2 hybrid nanomaterial loaded with Sn single atoms performs electrocatalytic hydrogen evolution reaction under full pH conditions and has excellent activity.

Citation Information

Patent Citations

  • Fe / Ni bimetallic MOF composite material loaded with 1T / 2H MoS2 heterojunction and preparation method thereof

    CN115161692A